(untitled) (Pedagogy of Higher and Secondary Education, 2009)
In the article an author examines the necessity of creation in the study process of situation of success for activation of cognitive activity, activity, increase of motivation of studies of junior schoolboys. Examining the methods of stimulation of educational activity, methode are directed on forming of positive reasons of studies points the specially developed structure of lesson in an initial link.